2017
DOI: 10.1002/celc.201600765
|View full text |Cite
|
Sign up to set email alerts
|

Poly(benzoxazine) as an Immobilization Matrix for Miniaturized ATP and Glucose Biosensors

Abstract: The reproducible immobilization of enzymes represents a key requirement in developing sensitive and fast‐responding amperometric microbiosensors. A microbiosensor for the respective detection of glucose and adenosine‐5′‐triphosphate (ATP) is presented by using a poly(benzoxazine) derivative for the entrapment of the enzymes glucose oxidase (GOD) and hexokinase (HEX) at platinum (Pt) microelectrodes (MEs). For glucose, a sensitivity of 123.05±10.78 pA/mM (n=5) was obtained, which shows twice as high sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Subsequent measurements of stretch‐induced ATP release using ATP microbiosensors 54 (Figure 5A) confirmed that ATP release from hAELVi cells is dependent on the expression of caveolin‐1 and Ca 2+ ‐entry via piezo1. ATP release from hAELVi wt and hAELVi cav−/− cells increased with increasing stretch amplitudes, however, release from hAELVi cav−/− was significantly lower.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Subsequent measurements of stretch‐induced ATP release using ATP microbiosensors 54 (Figure 5A) confirmed that ATP release from hAELVi cells is dependent on the expression of caveolin‐1 and Ca 2+ ‐entry via piezo1. ATP release from hAELVi wt and hAELVi cav−/− cells increased with increasing stretch amplitudes, however, release from hAELVi cav−/− was significantly lower.…”
Section: Resultsmentioning
confidence: 70%
“…ATP measurements were performed using an electrochemical biosensor based on surface immobilized glucose oxidase/hexokinase as recently described 54,55 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP microbiosensors were prepared by immobilizing glucose oxidase (from Aspergillus niger ; 1,500,000 U/g; Sigma-Aldrich Chemie) and hexokinase (from yeast; 2,500 IU solid; Calbiochem, Merck) in a poly(benzoxazine) layer ( Ziller et al, 2017 ) Pt microelectrodes with a radius of 25 µm were modified by electrodeposition using mixtures of BA-TEPA and GOD/HEX in a ratio of 1:2.5 wt/wt; the activity ratio for the two enzymes was 1:1. The synthesis of the precursor was prepared as previously described ( Andronescu et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, a very interesting transmembrane enzyme for biosensing is ATP-synthase or ATPase. The measurement of adenosin triphosphate (ATP) concentration is of great interest for studying cell metabolism [92] and for the detection of microbial contamination on surfaces [93]. In order to develop a sensitive and versatile biosensor for ATP detection, the ATPase from Escherichia coli was reconstituted on a floating phospholipid bilayer over a gold electrode modified with a 4-APh SAM ( Figure 5).…”
Section: Applications As Biosensorsmentioning
confidence: 99%